PERBANDINGAN STRATEGI PEMBELAJARAN MATEMATIKA DI KELAS RENDAH: STUDI OBSERVASI PADA PENGGUNAAN MEDIA LANTAI ANGKA DAN LIDI DI SDN 13/1 MUARA BULIAN - Anggia Tri Agustina; Silvina Noviyanti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Mathematics learning in lower grades requires a concrete, contextual approach that is appropriate for the cognitive development stage of early childhood. This study is an observational study conducted during an internship at SDN 13/1 Muara Bulian, specifically in grades 1A and 1B. The objective was to analyze and compare two mathematics learning strategies that used sensory-based media: a movement-based number floor (kinesthetic) in class 1A and sticks as concrete counting tools in class 1B. The results of the observation showed that both media were effective in helping students understand the concepts of addition and subtraction, although each had challenges in terms of classroom management and resource availability. This study also highlights the importance of the teacher's instructional assertiveness as the main foundation in learning in lower grades. These findings confirm that the teacher's creativity in choosing learning media that is appropriate to the local context and student characteristics is crucial to the success of mathematics learning at an early age.